Inhibition of adhesion, proliferation, and invasion of primary endometriosis and endometrial stromal and ovarian carcinoma cells by a nonhyaluronan adhesion barrier gel - Renner, Stefan; Strissel, Pamela; Beckmann, Matthias; Lermann, Johannes; Burghaus, Stefanie; Hackl, Janina; Fasching, Peter; Strick, Reiner (BioMed Research International, 2015)
Endometriosis is a chronic disease of women in the reproductive age, defined as endometrial cells growing outside of the uterine cavity and associated with relapses. Relapses are hypothesized to correlate with incomplete surgical excision or result from nonrandom implantation of new endometrial implants in adjacent peritoneum. Thus, surgical excision could lead to free endometriotic cells or tissue residues, which readhere, grow, and invade into recurrent lesions. Barrier agents are frequently used to prevent postoperative adhesions. We tested if the absorbable cell adhesion barrier gel Intercoat consisting of polyethylene oxide and sodium carboxymethyl cellulose could inhibit cellular adhesion, proliferation, and invasion of primary endometriosis and endometrial cells. Due to an association of endometriosis with ovarian carcinoma, we tested two ovarian carcinoma cell lines. Prior to cell seeding, a drop of the barrier gel was placed in cell culture wells in order to test inhibition of adherence and proliferation or coated over a polymerized collagen gel to assay for prevention of invasion. Results showed that the barrier gel significantly inhibited cell adherence, proliferation, and invasion of endometriosis and endometrial stromal cells as well as ovarian carcinoma cells in culture. Our findings could help to prevent local cell growth/invasion and possible consequent recurrences.
EVALuna2:17548